The Challenges of the teaching of RDA in librarianship courses: report of teaching experience at UFMG - Lourenço, Cíntia de Azevedo (2020)
The adoption of the RDA standard by Brazilian libraries is a reality that demands reflection and sharing of experiences. In this sense, the teaching of the RDA in librarianship courses is a priority to prepare future professionals for this transition and its implementation, but it also presents itself as a challenge. In this work, the experience of the librarianship course of a Brazilian university will be reported on the offer of a course to be introduced to the RDA, planned and implemented from the proposals presented in Margareth Mering's RDA teaching manual, published in English. The objective is to share the teaching experience, the results obtained and the difficulties encountered. The positive points of the manual, the difficulties of adapting the translation, the most interesting and challenging activities and the methodology will be highlighted. The final considerations highlight the limitations identified in this study and propose reflections on the implementation of the RDA. In addition, it will also be demonstrated that for teaching the signature will not be an necessity, which discourages the librarianship courses of this investment.